OPTIMALISASI JUMLAH PENGIRIMAN ROTI PT. NAJWA ROTI KE BEBERAPA DAERAH DENGAN MENGGUNAKAN METODE STEPPING STONE - Raihan Gading Rabbani; Rizki Nur Wakhid, Arif Bentar Suganda Heriyanto, Paduloh, Iskandar Zulkarnaen (CV. ADIBA AISHA AMIRA, 2024)
PT Najwa Roti is a company engaged in the distribution of bread located in Bekasi Regency. Based on interviews with the manager of PT Najwa Roti, it is known that currently the bread delivery process is not optimal. In this study, route optimization will be carried out by minimizing the distance of bread delivery done by PT. Najwa Roti using the stepping stone method. The stepping stone method is used to solve transportation problems with operating costs (factory and transportation) so that the shipping costs are relative. The business still uses a manual system to ship goods, but the computer system handles the data of shipping goods so that shipping goods can be done quickly and precisely. From our group discussion it can be concluded that the optimization of shipping costs from 8800 to 6770 which is the final result of optimizing the shipping costs.